TRANSFORMASI PENDIDIKAN CALON KATEKIS DAN GURU AGAMA KATOLIK DI ERA DIGITAL - Alexius Dwi Widiatna (Lembaga Penelitian STKIP Widya Yuwana, 2020)
The development and advancement of information and communication technology has permeated all aspects of human life today. Technological progress led to an industrial revolution and at the same time influenced the human lifestyle that formed the characteristics and character of a very varied generation. The character of this generation causes the world of education to adjust in terms of learning, teaching, pedagogy, and in the management of education. The church and its educational institutions are inseparable from the influence of advances in the digital world in educating young children in facing the challenges of 21st century education. As a higher education institution, STKIP Widya Yuwana is challenged to transform his learning in preparing his candidates of catechist and Catholic religion teachers who are digital generation or internet generation whose fingers are attached to their devices at any time. Creatively and collaboratively, educational persons are encouraged to build an atmosphere of freedom of learning by conducting digital metanoia and transforming themselves to be able to continue their preaching work to young people.